The Effects of pH and Excipients on Exenatide Stability in Solution - Alexander Benet; Troy Halseth; Jukyung Kang; April Kim; Rose Ackermann; Santhanakrishnan Srinivasan; Steven Schwendeman; Anna Schwendeman (MDPI AG, 2021)
Exenatide, a glucagon-like peptide-1 receptor agonist, is the active pharmaceutical ingredient in Byetta® and Bydureon®, two type 2 diabetes drug products that have generics and multiple follow-up formulations currently in development. Even though exenatide is known to be chemically and physically unstable at pH 7.5, there lacks a systematic evaluation of the impact of pH and excipients on the peptide solution stability. In this study, we established analytical methods to measure the chemical and physical degradation of the peptide in solution. Exenatide remained relatively stable at pH 4.5 when incubated at 37 °C. At pH 5.5-6.5, degradation was driven by oxidation, while driven by deamidation at pH 7.5-8.5. Significant aggregation of exenatide at pH 7.5 and 8.5 was detected by size exclusion chromatography and dynamic light scattering. Each pH value greater than 4.5 exhibited unique profiles corresponding to a loss of α-helical content and an increase in unordered structures. The addition of sugars, including mannitol, sorbitol and sucrose, conferred small protective effects against peptide aggregation when incubating at pH 7.5 and 37 °C, as measured by size-exclusion chromatography and dynamic light scattering. The results of this study will be useful for investigators developing generic exenatide products, peptide analogs and novel exenatide drug delivery systems.